Community Diagnosis in Banguntapan Village Bantul Regency, Yogyakarta - Rokhmayanti , Rokhmayanti; Wulandari, Ira Pebri; Fitriani, Dewi; Arfiiani, Ezra Sabrina; Pratiwi, Aulia Rahmadina; Puteri, Amelia Nurhaliza; Quratulain, Fitha Nurizza; Martini, Titim; Hastuti, Siti Kurnia Widi; Dwi Astuti, Fardhiasih (Universitas Ahmad Dahlan, 2024)
Background: Community diagnosis is an activity to identify problems by collecting data in the community that can locate broad issues and cover various aspects of society. The emergence of health problems is not only caused by individual negligence but can also be caused by community ignorance due to a lack of correct information about a disease. The purpose of this study is to obtain an overview of the health problems in Tegaltandan hamlet, Banguntapan sub-district to determine problem priorities and obtain appropriate alternative solutions to overcome the priority problems that have been resolved. Method: This study used descriptive quantitative analysis by conducting interviews using a community diagnosis questionnaire. The analysis was used to prioritize health problems using the USG method and village community meetings. The sampling technique was purposive sampling with 132 samples obtained. Results: Ten major health problems in the research area that need attention are no organic trash collection center covered in homes, using spray-repellent, not used to wearing a helmet during riding, not sprinkling larvacide powder on the washed water dump as dengue prevention, not applying repellents as dengue prevention not using gloves while chopping ingredients with a knife for cooking, no props when moving heavy objects, not taking care of fish larvae eaters, hypertension and diabetes mellitus. After prioritizing using USG and village community meetings, they all agreed to decide diabetes mellitus as the main health problem in this area. Conclusion: Diabetes mellitus was considered a major problem at the study site that requires further intervention.